2020
DOI: 10.1038/s41598-020-77319-0
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolic profiling provides diagnostic and prognostic information in critically ill children with suspected infection

Abstract: Sepsis, defined as life-threatening organ dysfunction caused by infection is difficult to distinguish clinically from infection or post-operative inflammation. We hypothesized that in a heterogeneous group of critically ill children, there would be different metabolic profiles between post-operative inflammation, bacterial and viral infection and infection with or without organ dysfunction. 1D 1H nuclear magnetic resonance spectra were acquired in plasma samples from critically ill children. We included childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…It is suggested that mitochondrial dysfunction in sepsis leads to the accumulation of glycolysis and tricarboxylic acid (TCA) cycle metabolites such as lactate, pyruvate and citric acid [ 16 ], and the pathways which lead to the accumulation of these metabolites are shown in Figure 1 . Several studies in Table 1 consistently showed that sepsis patients had increased levels of glycolysis metabolites including lactate [ 21 , 22 , 23 , 24 , 25 ] and pyruvate [ 21 , 26 ] compared to healthy controls [ 21 , 22 , 23 ] or those with SIRS [ 24 , 25 , 26 ]. Lin et al showed elevation of seven TCA metabolites as well as two TCA cycle derivatives including DL-gamma-methylketoglutaramate isomer and dimethyl fumarate in sepsis compared to healthy controls [ 21 ], which suggests upregulation of the TCA cycle in septic patients.…”
Section: Metabolomics To Identify Diagnostically Useful Clinical Phen...mentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that mitochondrial dysfunction in sepsis leads to the accumulation of glycolysis and tricarboxylic acid (TCA) cycle metabolites such as lactate, pyruvate and citric acid [ 16 ], and the pathways which lead to the accumulation of these metabolites are shown in Figure 1 . Several studies in Table 1 consistently showed that sepsis patients had increased levels of glycolysis metabolites including lactate [ 21 , 22 , 23 , 24 , 25 ] and pyruvate [ 21 , 26 ] compared to healthy controls [ 21 , 22 , 23 ] or those with SIRS [ 24 , 25 , 26 ]. Lin et al showed elevation of seven TCA metabolites as well as two TCA cycle derivatives including DL-gamma-methylketoglutaramate isomer and dimethyl fumarate in sepsis compared to healthy controls [ 21 ], which suggests upregulation of the TCA cycle in septic patients.…”
Section: Metabolomics To Identify Diagnostically Useful Clinical Phen...mentioning
confidence: 99%
“…S-(3-methylbutanoyl)-dihydrolipoamide-E, a metabolite involved in the degradation of BCAAs ( Figure 1 ) was elevated in sepsis patients compared to SIRS [ 34 ]. Moreover, the levels of isoleucine and leucine were reduced in septic infant [ 25 ] and paediatric populations [ 24 ] compared to controls, perhaps suggesting differences in metabolism between children and adults. Alterations in aromatic amino acids may relate to the increase in oxidative stress ( Figure 1 ) with phenylalanine being higher in septic patients compared to healthy controls [ 21 , 37 , 38 ] those with SIRS [ 20 , 25 , 32 ] and in mechanically ventilated patients with pneumonia compared with those with brain injuries [ 40 ].…”
Section: Metabolomics To Identify Diagnostically Useful Clinical Phen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Arturas Grauslys used NMR to study 55 infected children (25 bacterial infections, 30 viral infections) and 58 uninfected children undergoing heart surgery. The results showed that metabolomics can distinguish children with infection from children with postoperative inflammation but no infection [40]. James R. Anderson used NMR technology to analyze the synovial tissue of horses.…”
Section: Application Of Metabolomics In Sepsis 31 Application Of Metabolomics In the Diagnosis Of Sepsismentioning
confidence: 99%